Alternative Sets in Language Processing : How Focus Alternatives are Represented in the Mind - Gotzner, Nicole (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book presents a novel experimental approach to investigating the mental representation of linguistic alternatives. Combining theoretical and psycholinguistic questions concerning the nature of alternative sets, it sheds new light on the theory of focus and the cognitive mechanisms underlying the processing of alternatives. In a series of language comprehension experiments, the author shows that intonational focus and focus particles such as 'only' shape the representation of alternatives in a listener's mind in a fundamental way. This book is relevant to researchers interested in semantics, pragmatics, language processing and memory. Nicole Gotzner is a postdoctoral researcher at the Centre for General Linguistics (ZAS) in Berlin, Germany. She is affiliated with the DFG Priority Programme Xprag.de "New Pragmatic Theories Based on Experimental Evidence". Her research combines semantic and pragmatic theory with language processing and child language acquisition.
Keywords: Linguistics.; Phonology.; Psycholinguistics.; Semantics.; Pragmatics.; Cognitive grammar.; elektronické knihy; electronic books